Pengembangan Sumber Daya Manusia Aparatur Sipil Negara pada Dinas Pemuda dan Olahraga Kota Palu: Human Resource Development of State Civil Apparatus at the Palu City Youth and Sports Service - M. Rizky Fauzi; Syahruddin Hattab; Nuraisyah (Pendidikan Al-Gafari, 2026)
Human resource development has been widely implemented in various types of organizations, both in the education, government, and private sectors. This study aims to determine the development of human resources of the State Civil Apparatus at the Palu City Youth and Sports Office. This study uses a descriptive method with a qualitative approach. The research informants numbered 6 people who were selected purposively. Data collection techniques were carried out through interviews, observation, and documentation. The analysis used which includes education, training, career development, competency development, and HR development. The results of the study indicate that ASN human resource development has been ongoing but is not yet optimal in several aspects, especially training and competency development.